Abberantly placed impacted mandibular canine - Rashi Bahl; Jeetinder Singla; Mohita Gupta; Ankit Malhotra (Wolters Kluwer Medknow Publications, 2013)
Pre-eruptive migration of a tooth across the midline is termed as transmigration. It is believed that transmigration is rare and unique to the mandibular permanent canines, and even more rarely reported for others. Transmigration is a phenomenon of yet unknown etiology. It follows the direction of its long axis, with the crown leading the migration. The tendency of a canine to cross the barrier of mandibular midline suture is a more important consideration than the distance of migration after crossing the midline. Here we present one new case of aberrantly positioned right mandibular canine which has undergone migration and was accidently found on radiological examination before orthodontic treatment. Once diagnosed an aberrantly positioned impacted canine requires surgical removal.